Methodological approaches to prevention of radiation-induced skin reactions in neutron-photon therapy for malignant neoplasms - E. L. Choynzonov; V. A. Lisin; О. V. Gribova; V. V. Velikaya; Zh. А. Startseva (Сибирский онкологический журнал)
The goal of radiotherapy is to maximize the radiation dose to abnormal cancer cells while preventing damage to healthy tissue. in neutron therapy, the optimum regime of treatment is uncertain to date.The purpose of the study to develop a set of methodological approaches that ensure the permissible frequency and severity of radiation-induced reactions in cancer patients subjected to neutron and neutron-photon therapy (NFt) using u-120 cyclotron.Material and methods. We used the dependence of the relative biological effectiveness (RBE) of neutrons on the dose and time-dose-fractionation model (tdF). the interaction of neutrons with various types of tissues was analyzed, and the algorithm for summing neutron and photon doses in neutronphoton therapy was developed.Results. Clinical studies of neutron-photon therapy showed that the developed approaches can predict and prevent serious damage to normal tissue with a satisfactory accuracy. the role of all factors influencing the nature of radiation reactions was taken into account in the computer program, which allowed the main characteristics of the planned courses of neutron-photon therapy to be obtained.